New Frontiers on Seismic Modeling of Masonry Structures - Caddemi, Salvatore; Caliò, Ivo; Cannizzaro, Francesco; Pantò, Bartolomeo (Frontiers in Built Environment, 2017)
An accurate evaluation of the nonlinear behaviour of masonry structural elements in existing buildings still represents a complex issue that rigorously requires nonlinear finite element strategies difficult to apply to real large structures. Nevertheless, for the static and seismic assessment of existing structures, involving the contribution of masonry materials, engineers need reliable and efficient numerical tools, whose complexity and computational demand should be suitable for practical purposes. For these reasons the formulation and the validation of simplified numerical strategies represents a very important issue in masonry computational research. In this paper an innovative macro-element approach, developed by the authors in the last decade, is presented. The proposed macro-element formulation is based on different, plane and spatial, macro-elements for the simulation of both the in-plane and out-of-plane behaviour of masonry structures also in presence of masonry elements with curved geometry. The mechanical response of the adopted macro-element is governed by nonlinear zero-thickness interfaces, whose calibration follows a straightforward fibre discretization, and the nonlinear internal shear deformability is ruled by equivalence with a corresponding geometrically consistent homogenized medium. The approach can be considered as ‘parsimonious’ since the kinematics of the adopted elements is controlled by very few degrees of freedom, if compared to a corresponding discretization performed by using nonlinear FEM strategies. This innovative discrete-element strategy has been implemented in two user-oriented software codes 3DMacro and HiStrA (Historical Structures Analysis), which simplifies the modelling of buildings and historical structures by means of several wizard generation tools and input/output facilities. The proposed approach, that represents a powerful tool for the structural assessment of structures in which the masonry plays a key role, is here validated against experimental results involving typical masonry monumental sub-structural elements and numerical results involving real-scale structures.